Individual differences in same-different evaluation of figures when they are presented simultaneously or successively - Šoliūnas, Alvydas; Gurčinienė, Ona (Psichologija, 2005)
It is known that in same-different task, in which the subject must answer whether two presented stimuli are the same or different, the performance of the subjects can achieve two different modes – holistic and analytic. The other question is how the estimation of stimuli sameness depends on two prevailing methods used in same-different task – successive and simultaneous stimuli presentation. The purpose of this paper was to investigate whether the different modes in subject’s performance depend on these two methods of stimuli presentation. Psychophysical same-different experiment was performed in which the pairs of irregular polygons were presented simultaneously or successively. Five groups of stimuli pairs with different degree of reciprocal similarity were composed from the set of 12 polygons. Three interstimulus intervals were used under successive presentation conditions: 500 ms, 1000 ms, and 1500 ms. Stimuli were presented briefly (for 67–350 ms under simultaneous and for 33–100 ms under successive presentation conditions, and this time interval was established individually during training sessions) on computer screen. The subjects were required to answer whether two figures were the same or different. Under successive presentation conditions, the subjects fell into two different groups. For the majority of subjects, the performance directly depended on the degree of similarity between two figures – the more the figures were similar the longer the reaction time was and the more mistakes the subjects made. For other subjects, the performance accuracy but not the reaction time depended on the degree of figure similarity. Performance of these two groups of subjects could be attributed to the analytic and holistic strategies respectively. Under simultaneous presentation conditions, the subjects’ performance clearly did not split into two different modes: both the reaction time and performance accuracy depended on the degree of similarity of two figures. This result could suppose that all subjects probably use analytic strategy when compare two simultaneously presented stimuli. The practice under simultaneous presentation conditions and the difference in interstimulus interval under successive presentation conditions did not effect the character of the dependence of the accuracy and reaction time of the estimation of figure sameness, and the only effect was that the reaction time decreased with practice and increased with longer interstimulus intervals.